Comparative analysis of community composition and network structure between phyllosphere endophytic and epiphytic fungal communities of Mussaenda pubescens - Deqiang Chen; Juanjuan Yang; Shunfen Wang; Siren Lan; Yonglong Wang; Zhong-Jian Liu; Xin Qian (Microbiology Spectrum)
ABSTRACT The phyllosphere constitutes a critical habitat for microorganisms, exerting profound influences on host vitality, developmental dynamics, reproductive functions, and stress resilience. However, the diversity and network structure of endophytic and epiphytic fungal communities within this microecosystem have not been thoroughly explored. In this investigation, high-throughput sequencing technologies were employed to assess the diversity, community composition, and network structure of endophytic and epiphytic fungal communities associated with Mussaenda pubescens across six geographically distinct locations in Southeast China. The results revealed significant differences in community composition and diversity between endophytic and epiphytic fungi, with pronounced geographical variation observed within these phyllosphere fungal communities. Network analysis indicated that epiphytic fungal networks possess enhanced complexity compared with their endophytic counterparts, although the latter exhibit greater network stability. Moreover, stochastic processes were identified as pivotal in shaping the composition of these fungal communities. This research substantially enriches our comprehension of the diversity and organizational mechanisms of phyllosphere fungal communities, providing novel insights into the modalities of species coexistence and the stability of community equilibrium within ecosystems.IMPORTANCEThis study employs high-throughput sequencing technologies to explore the fungal communities within the phyllosphere of Mussaenda pubescens across Southeast China, offering significant insights into plant mycobiome. It demonstrates geographical variations in these fungal communities, with epiphytic fungi exhibiting more complex interaction networks compared with the endophytic fungi. Crucially, the research indicates that stochastic processes play a substantial role in the composition of fungal communities. These findings enhance our comprehension of plant-associated microecosystems and underscore the intricate interplay of randomness in maintaining ecosystem stability and diversity.